Reproductive Health Problems and Treatment Seeking Behavior Among Adolescent Girls of UHTC Field Practice Area, Govt. Medical College, Bhavnagar - Mansi G Chauhan; Harshad Patel (Medsci Publications, 2016)
Background: Within the family, compared to boys, the 'adolescent girls' health, nutrition, education & development are more neglected and it has adverse effect on reproductive health. This study was conducted to assess awareness about reproductive health among adolescent girls & to study prevalence of reproductive health problems & treatment seeking behavior among adolescent girls for Reproductive Tract Infections (RTIs). Materials & methods: Community based cross sectional study was conducted among 532 Adolescent girls during February 2014 to August 2014. Data was collected by pretested prestuctured questioner. Results: One or more symptoms of reproductive tract infections were found among 36.65% adolescent girls amongst them vaginal discharge was most common among 81(41.53%) girls. Only 12.83% girls sought treatment for RTI. Age of girl, educational status of girl, religion & socioeconomic class have association with development of reproductive tract infection. (p<0.05) Conclusion: Prevalence of RTI among adolescent girls is 36.65%. Treatment seeking behavior is found in only 12. 83% among them. Sociodemographic factors have impact on developing reproductive tract infection.